A republic of garden city-states on which the sun never sets: A republic of garden city-states on which the sun never sets: - Wilson, Matthew (International Planning History Society Proceedings, 2018)
From the mid 1850s and into the interwar period a little-known group of citizen-sociologists attempted to break up the British Empire and establish a proto- garden-city-state network. These actors were the followers of the French Positivist philosopher Auguste Comte and his British acolyte Richard Congreve. Comte introduced the modern science of sociology, the Religion of Humanity, and the utopia called the Occidental Republic. After setting out the socio-spatial character of this utopia, this study will argue that from the 1850s the former Oxford don and ex-Anglican minister Richard Congreve advocated Comte’s principles as British international and national policy. I will contend that Congreve’s affiliates formed an organised resistance to imperialism, exploitation, poverty, and despondency. They created urban interventions or Positivist institutes, led ad hoc sociological surveys, and published programmes for realising regional republics. This essay contributes to our understanding of how Positivist sociology was a eutopian spatial design practice rooted in creating a comprehensive and participatory moral, cultural and intellectual network for the life virtuous. If we require some alternative to religious fanaticism, political lethargy, provincialism, fake news and right-wing reaction, the praxis explored herein might serve as a precedent for ethical, political and collectivist spatial agency.